Ecoprint Business Development at Newcoral Ecofriendly UMKM trhough Improving Production, Management and Marketing Quality - Rahmawati, Rahmawati; Wahyuningsih, Sayekti; Amperawati, Endang Dwi; Samsi, Samsi; Paramita, Ratna Wijayanti Daniar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) newcoral ecofriendly is a business engaged in the production of other ecoprints based on natural materials such as leaves, twigs, flowers, and roots. The ecoprint products produced have high artistic value and are environmentally friendly, making them one of the leading business opportunities in the creative industry. However, this MSME faces a number of problems that hinder business development, including inconsistent production quality, less structured business management, and limited marketing strategies. The method implemented in community partnership empowerment-based service in the form of workshop activities, mentoring in ecoprint making practices, providing training related to management governance and marketing processes, as well as monitoring and evaluation. This program is expected to produce outputs in the form of scientific publications, media publications, and videos. Through this activity, Usaha Mikro, Kecil, dan Menengah (UMKM) newcoral ecofriendly is expected to be able to increase competitiveness and contribute to the development of environmentally friendly creative industries in Indonesia.